The Influence of Human Resource Development and Work Motivation on Employee Performance in the NCVS 1.07 Assembling Section at PT Adis Dimension Footwear, Tangerang Regency - Fatoni, Muhammad Yen; Fahmi, Khaerul (Faculty of Science and Technology University of Pramita Indonesia, 2026)
The purpose of this study was to determine how much influence HR development and work motivation simultaneously have on employee performance in the NCVS 1.07 Assembling section at PT. Adis Dimension Footwear Tangerang Regency.This study uses a quantitative descriptive method. The research sample consisted of 80 respondents.The results of this study indicate that (1) partially, human resource development significantly affects employee performance in the Assembling NCVS 1.07 section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the t count value> t table (6.641> 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work motivation significantly affects employee performance in the Assembling NCVS1.07 section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the t count value> t table (5.786> 1.991) and the significance value of 0.000 is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, human resource development and work motivation significantly influence employee performance in the Assembling NCVS 1.07 section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount> Ftable (97.882>3.15) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of human resource development and work motivation, both partially and simultaneously, have a significant influence on employee performance in the Assembling NCVS 1.07 section at PT. Adis Dimension Footwear, Tangerang Regency